Impacts of Culturo-Techno-Contextual Approach on Critical Thinking of Secondary School Students in Learning Difficult Concepts in Physics - Akintoye, Hakeem Olanrewaju; Elemoro, Sodiq Adewale; Ogunyemi, Temitope Gabriel (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
This study examined the impact of Culturo-Techno-Contextual Approach(CTCA) on the critical thinking of secondary school students in learning difficult concepts in physics. The study employed a mixed-methods approach. The quantitative approach employed the pre-test, post-test and control group quasi-experimental design, while the qualitative approach employed a semi-structured interview for data collection. A total of eighty senior secondary school physics students were selected from a sampled school in Education District V of Lagos state. The research instruments titled Physics Critical Thinking Test(PCCT) and Physics Students Semi-Structured Interview Schedule(PSSIS) were used for data collection. Three research questions were raised and three null hypotheses were tested. The data collected were subjected to one-way and two-way analysis of covariance (ANCOVA) respectively using IBM-SPSS version 23 while the research questions were descriptively analyzed. Findings from this study revealed that CTC Approach has a huge impact on students' critical thinking, it measures success at determining the cognitive effect on students. It also revealed that there will be no statistically significant impact of sex and methods of teaching (CTCA and lecture) on the critical thinking of students in physics difficult concepts. The study further revealed that methods and sex were not statistically significant on the critical thinking of students in physics difficult concepts. Based on the findings it was concluded that the CTC Approach is suitable for killing all illnesses affecting productive and efficient teaching and learning of physics difficult concepts. It was further realized from the study that both males and females will learn at the same pace and either of the two methods will have no effects on the student's critical thinking, so as to improve or deteriorate it. Finally, from the interview conducted, the teachers opined that effective application of the CTC Approach will bring about a massive increase in students' critical thinking, make them be confident scientists and technologists, capable of increasing students' enrolment in physics with improvements in the academic performance of the students. Therefore, it was recommended amongst others that the use of CTCA as an instructional strategy should be explored by physics teachers to enhance meaningful learning of difficult concepts, with physics teachers well trained in content and pedagogy where teachers learn and understand the rudiment and application of CTCA.